The new approach of Rijndael key schedule - Sulaiman, Salasiah; Muda, Zaiton; Juremi, Julia (IEEE, 2012)
The key schedule function in Rijndael block cipher did not receive the same amount of attention during design as the cipher components. Based on our research, there are several properties in key schedule that seemed to violate the design criteria, which was published by NIST, and this has lead to many types of attack performed on Rijndael block cipher. The aim of this research is to produce a new key schedule algorithm, an enhancement from the Rijndael key scheduling, which follows the principle of secure cipher by Shannon, where the new key schedule must satisfy the bit confusion and diffusion properties for security purpose. After both keys from schedule algorithms (Rijndael and the proposed approach) have been analyzed, the results show that the proposed approach satisfies the requirement that set by Shannon in achieving both of the properties.